2002
DOI: 10.1073/pnas.112276199
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal domain phosphatase-like family members (AtCPLs) differentially regulateArabidopsis thalianaabiotic stress signaling, growth, and development

Abstract: Cold, hyperosmolarity, and abscisic acid (ABA) signaling induce RD29A expression, which is an indicator of the plant stress adaptation response. Two nonallelic Arabidopsis thaliana (ecotype C24) T-DNA insertional mutations, cpl1 and cpl3, were identified based on hyperinduction of RD29A expression that was monitored by using the luciferase (LUC) reporter gene (RD29A::LUC) imaging system. Genetic linkage analysis and complementation data established that the recessive cpl1 and cpl3 mutations are caused by T-DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
185
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 146 publications
(189 citation statements)
references
References 58 publications
3
185
1
Order By: Relevance
“…Allelism tests found six new fry2 alleles, which were named as fry2-2 through fry2-7. Quantitation of luminescence expression in these mutants indicates that the average luminescence intensities in these mutants are [11][12][13][14][15][16][17][18][19][20][8][9][10][11], and 15-21 times higher than those in the wild type under cold, ABA, and NaCl treatments, respectively. The intensities for the nonstress control treatment are only 1.6-4.1 times higher in fry2 mutants than in the wild type (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Allelism tests found six new fry2 alleles, which were named as fry2-2 through fry2-7. Quantitation of luminescence expression in these mutants indicates that the average luminescence intensities in these mutants are [11][12][13][14][15][16][17][18][19][20][8][9][10][11], and 15-21 times higher than those in the wild type under cold, ABA, and NaCl treatments, respectively. The intensities for the nonstress control treatment are only 1.6-4.1 times higher in fry2 mutants than in the wild type (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For reciprocal cross analysis, a fry2-1͞ϩ cpl2-2͞ϩ plant and a fry2-1 plant were used as parents. F 1 seedlings with homozygous fry2-1 genotype were selected by using RD29a-LUC expression after cold and ABA treatments as described (5,6). The fry2-1 phenotype of the F 1 plants indicated that the gametes from the diheterozygous parent contained the fry2-1 chromosome.…”
Section: Methodsmentioning
confidence: 99%
“…The stress-inducible promoter of the RD29a gene contains dehydration͞cold-responsive elements and ABA-responsive elements that are the targets of distinct families of DNA binding transcription factors (1,2). The plant stress response is also regulated by proteins that impact the core RNA polymerase II (Pol II) transcriptional machinery, the mRNA maturation process, and chromatin structure (3)(4)(5)(6)(7)(8)(9). Analysis of Arabidopsis mutants that display hyperinduction of RD29a expression under stress conditions have identified a family of C-terminal domain (CTD) phosphatase-like (CPL) genes that negatively regulate stressresponsive transcription (5,6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Seedlings were transferred to basal medium supplemented with 160 mM NaCl or various concentrations of other compounds, and root growth was scored 8 days later. RD29a-LUC expression was monitored with a charge-coupled device imaging system (Roper Scientific, Trenton, NJ) after seedlings were subjected to cold (0ЊC, 2 days), abscisic acid (100 M, 4 h), or NaCl (300 mM, 4 h) treatment (Ishitani et al, 1997;Koiwa et al, 2002).…”
Section: Isolation Of Salt-hypersensitive Mutants and Growth Measuremmentioning
confidence: 99%